Effect of early shearing during gestation on the productive and reproductive behavior of female sheep offspring in their first 18 months of age - López-Mazz, C.; Baldi, F.; Quintans, G.; Kenyon, P. R.; Correa, O.; Regueiro, M.; Álvarez-Oxiley, A.; Banchero, G. E. (Elsevier, 2020)
The research has shown the interesting contributions of shearing in mid-gestation on the performance of lambs from birth to weaning. Other studies have reported that shearing at early pregnancy influences the development of the placenta and lamb live weight at birth. However, there was a lack of information on the effect of early-prepartum shearing on the behavior of the offspring from weaning onward. This study evaluated the effect of shearing ewes at 50 days of gestation on the growth, reproductive behavior and response to a gastrointestinal parasite challenge in the female offspring from weaning to 18 months old. Fifty-seven Polwarth female lambs were used, 22 being singles and 35 twins born to ewes either shorn at 50 days of pregnancy (PS, n = 23) or shorn at 62 days postpartum (U, control, n = 34) resulting in four subgroups: single lambs born to PS ewes (n = 8), born to U ewes (n = 14), twin lambs born to PS ewes (n = 15) or born to U ewes (n = 20). All progeny were managed together under improved pasture with a minimum forage allowance of 6% live weight on dry basis. Body weight, body condition score and fecal eggs count were recorded every 14 days from weaning to 18 months of age. Concentrations of progesterone were measured weekly (from 4 to 10 months of age and from 14 to 18 months of age) to establish the onset of puberty. Ovulation rate at an induced and a natural heat (545 ± 1.0 and 562 ± 1.0 day old) was recorded. Prepartum shearing did not affect the age at puberty or the ovulation rate of female offspring, but those born as singles were more precocious ( P = 0.03) and heavier ( P = 0.02) at puberty than twin born lambs. Both the average value of parasite egg count ( P = 0.0 7) and the Famacha index ( P = 0.02) for the entire study period were lower in lambs born to prepartum shorn ewes than those born to postpartum shorn ewes. In conclusion, shearing at 50 days of gestation did not affect the growth or the reproductive behavior of female offspring. However, female lambs born from ewe shorn during gestation showed a better response to the parasitic challenge, and further research is required to confirm this.
Keywords: early shearing; female progeny; growth; immunity; reproduction